Antibody screening tests variably overestimate the prevalence of hepatitis C virus infection among HIV‐infected adults in Ghana. Issue 5 (14th November 2014) - King, S.; Adjei‐Asante, K.; Appiah, L.; Adinku, D.; Beloukas, A.; Atkins, M.; Sarfo, S. F.; Chadwick, D.; Phillips, R. O.; Geretti, A. M.
Summary HIV coinfection with HCV has been poorly studied in sub‐Saharan Africa, and the reliability of available seroprevalence estimates remains uncertain. The study aim was to determine HCV RNA prevalence in HIV‐infected subjects receiving care in Kumasi, Ghana, and relate the findings to HCV antibody detection. From a population of 1520 HIV‐infected adults, all HBsAg‐positive subjects (n = 236) and a random subset of HBsAg‐negative subject (n = 172) were screened for HCV RNA using pooled plasma; positive samples were genotyped by core and NS5B sequencing. HCV antibodies were detected by three commercial screening assays and confirmed by the line immunoassay. HCV RNA was detected in 4/408 subjects (1.0%, 95% confidence interval 0.0–1.9%), comprising 3/236 (1.3%; 0.0–2.8%) HBsAg‐positive and 1/172 (0.6%; 0.0–1.8%) HBsAg‐negative subjects. HCV RNA‐positive subjects showed reactivity in all three antibody screening assays. Among HCV RNA‐negative subjects, 5/67 (7.5%), 5/67 (7.5%) and 19/67 (28.4%) showed antibody reactivity by each screening assay, respectively, including two (3.0%) with reactivity by all three assays. Only one sample (1.5%) had confirmed antibody reactivity by line immunoassay indicating past HCV infection. HCV‐positive subjects (three males, two females) were aged 30–46 years, by questionnaire‐based interview reported surgical procedures and blood transfusion as risk factors for infection. HCV genotypes were 2 (subtypes 2j, 2l, 2k/unassigned) and 1 (subtype unassigned). Without further testing, HCV antibody screening assays variably overestimated HCV prevalence among HIV‐infected subjects in Ghana. These findings inform the interpretation of previous seroprevalence estimates based upon screening assays alone.